A preliminary study of sustainable transport indicators in Malaysia: the case study of Klang Valley public transportation - Bachok, Syahriah; Ponrahono, Zakiah; Mohamed Osman, Mariana; Jaafar, Samsuddin; Ibrahim, Mansor; Mohamed, Mohd Zin (Elsevier, 2015)
This research centers around the exploration of the applicability and transferability of some international/global sustainable transport indicators in an important city region in Malaysia, namely Klang Valley. The literature review highlights several important measures to identify, determine and select the relevant sustainable transportation indicators. Around 30 out of 1000 indicators were chosen to be tested in the different scenarios of public transportation in Malaysia. The research applied the snowball internet survey method, in addition, face-to-face, snail-mail, and electronic questionnaire. Samples were selected from a list of various professionals relevant to the field of transportation. They include transport planners, traffic engineers, public transport operators and managers, transportation economists, environmentalists, academician and researchers, as well as urban and regional planners. It is found that a number of indicators such as the percentage of bus passenger is suitable and relevant to Klang Valley. However, several other indicators are deemed less suitable to represent the measurement of sustainability of transportation in Klang Valley. Hence, it is suggested by the research that future selection of indicators should have a greater sensitivity to be more realistic with the country current situations, circumstances and fortune. Preliminary findings of the research are intended to be disseminated through another set of focus group discussion.